DESAIN DAN ANALISIS NUMERIK CONTRA ROTATING DUCTED FAN UNTUK UAV - Auliaarrahman Utomo, Rifqi
Currently, a need for unmanned aerial vehicles (UAVs) continues to increase from time to time. One of the needs for UAV procurement in Indonesia at this time is the need for EDF with a thrust requirement of 250 N. So that to make the EDF and can be produced domestically, in this final project, the authors designed a contra-rotating ducted fan thruster by combining two motors that can accommodate a thrust of 250 N. The design of the thruster chosen is the contrarotating ducted fan (CRDF) because one of its advantages is the additional thrust of the duct and the contra-rotating fan scheme which allows the fan to generate additional thrust with the same fan diameter. CRDF blades are designed using blade element momentum theory, the CRDF geometry is then simulated using computational fluid dynamic. The influence of the duct design with the design parameter of the expansion ratio and opening angle was also searched using CFD simulation. The results of this final project research indicate that the CRDF design type can be used to design a UAV thruster with a thrust target of 250 N and power required below 15 kW, and the duct design has a major contribution to the achievement of CRDF design targets.